2011
DOI: 10.1186/1756-3305-4-8
|View full text |Cite
|
Sign up to set email alerts
|

The combination of the entomopathogenic fungus Metarhizium anisopliae with the insecticide Imidacloprid increases virulence against the dengue vector Aedes aegypti (Diptera: Culicidae)

Abstract: BackgroundDengue fever transmitted by the mosquito Aedes aegypti, is one of the most rapidly spreading insect borne diseases, stimulating the search for alternatives to current control measures. The dengue vector A. aegypti has received less attention than anophelene species, although more than 2.5 billion people are at risk of infection worldwide. Entomopathogenic fungi are emerging as potential candidates for the control of mosquitoes. Here we continue our studies on the pathogenicity of the entomopathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 30 publications
0
52
0
4
Order By: Relevance
“…These dead mosquito larvae were placed in the Saboraud dextrose agar (SDA) plates supplemented with chloramphenicol (25 毺g/mL) as a bacteriostatic agent according to the method of Paula et al with some modification [13] . Incubator was used for incubation of these plates with larvae for 5 days, which was maintained at (24暲2 曟 ).…”
Section: Isolation Of Entomopathogenic Fungusmentioning
confidence: 99%
“…These dead mosquito larvae were placed in the Saboraud dextrose agar (SDA) plates supplemented with chloramphenicol (25 毺g/mL) as a bacteriostatic agent according to the method of Paula et al with some modification [13] . Incubator was used for incubation of these plates with larvae for 5 days, which was maintained at (24暲2 曟 ).…”
Section: Isolation Of Entomopathogenic Fungusmentioning
confidence: 99%
“…2). 290 Lee et al Nomuraea rileyi는 30종이 넘는 나비목 유충에 대한 병원성을 보이며 밤나방과(Noctuidae)에 속하는 유충들에 감염을 잘 일으 켜 난방제 나비목 해충 방제를 위해서 많은 연구가 이루어 지고 있다 (Ignoffo, 1981;Ignoffo and Boucias, 1992;Sanchez-Peña, 2000;Martins et al, 2005). (Jaramillo et al, 2005;Santos et al, 2007;Brito et al, 2008;Paula et al, 2011;Sun et al, 2012). 또한 다른 친환경 방제제인 여러 가지 친환경 추출물 또는 천적 곤충과 곰팡이 살충제를 함 께 처리함으로써 곰팡이 살충제의 낮은 살충력을 보완 하면서 동시에 두 가지 모두 살충효과를 높일 수 있는 것에 대해 많은 연 구가 활발히 이루어지고 있다 (Wekesa et al, 2007;Rashki et al, 2009;Park and Kim, 2012).…”
Section: 고 찰unclassified
“…Studies have showed that A. aegypti had significantly increased mortality after exposure to M. anisopliae (Scholte, et al 2007;de Paula, et al 2008 and B. bassiana (de Paula, et al 2008. Worryingly, susceptibility to fungal infection is significantly reduced following a blood meal, but after digestion fungal susceptibility returned to pre-feeding levels (de Paula, et al 2011a). Also wild strains may be less susceptible to fungal infection than some colony strains used (de Paula, et al 2011b).…”
Section: Fungi (Ascomycetes: Hypocreales)mentioning
confidence: 99%